Pendidikan Karakter Dalam Perspektif Habib Abdullah bin Alwi Al-Haddad - Ahmad Avisena (Research Department (Lemlit) Islamic Institute of Darullughah Wadda’wah Bangil, Pasuruan, 2018)
Character education is one of the concrete steps that must be done to protect Indonesian future generations. Habib Abdullah bin Alwi al-Haddad as an educator has been conceptualized character education that proved successful on his era. This study aimed to describe and assess three things. First, the purpose of education in the perspective of the character of Habib Abdullah bin Alwi al-Haddad. Second, the main character values in the perspective Habib Abdullah bin Alwi al-Haddad. Third, character education strategy in the perspective Habib Abdullah bin Alwi al-Haddad. This study is a qualitative research, with the kind of individual life history and a thematic approach. Documentation method used as its data collection that divided into primary and secondary data. While the domain analysis become its analysis technique. In this study, researchers found that the purpose of the character education perspective Habib Abdullah bin Alwi al-Haddad is to help someone who wants to be loved by Allah. While the main character values in his perspective is piety which has five main indicators that is honesty, patience, gratitude, fairness and concern. As for character education strategies in his perspective is consist of five steps, introduction, motivation, conditioning, habituation and prayer.